2016
DOI: 10.1177/1357633x16632968
|View full text |Cite
|
Sign up to set email alerts
|

Education and training to support the use of clinical telehealth: A review of the literature

Abstract: Introduction Despite a growing literature base, substantial investment, and policy changes within governments, the integration of telehealth into routine clinical care has been limited. The availability of appropriate systematic education and training for practitioners has been highlighted as necessary for strong adoption. However, the availability and nature of telehealth-related education and training for practitioners is not understood. By reviewing the literature, we aimed to describe the delivery of educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
200
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(212 citation statements)
references
References 23 publications
6
200
0
6
Order By: Relevance
“…Five of the studies described short continuing education programs3–7 and only six described formal university programs8–13 with three being with nurse practitioners 9,11,12. Compared to other aspects of telehealth research (i.e., feasibility, effectiveness, economics, and satisfaction), literature related to education and training in telehealth has remained scant 14. This may be due to many providers being unacquainted with telehealth or perhaps a lack of interest in the field, secondary to this limited experience 15,16.…”
Section: Gaps In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Five of the studies described short continuing education programs3–7 and only six described formal university programs8–13 with three being with nurse practitioners 9,11,12. Compared to other aspects of telehealth research (i.e., feasibility, effectiveness, economics, and satisfaction), literature related to education and training in telehealth has remained scant 14. This may be due to many providers being unacquainted with telehealth or perhaps a lack of interest in the field, secondary to this limited experience 15,16.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Telehealth programs have been used to provide content that focuses on 1) defining telehealth, 2) telehealth etiquette, 3) interprofessional collaboration, 4) regulations, 5) reimbursement, 6) security/Health Insurance Portability and Accountability Act (HIPAA), 7) ethical practice in telehealth, and 8) satisfaction 14,15,17,23–25. The following sections address recommended topics that programs might consider addressing when training nurse practitioners in telehealth.…”
Section: Topicsmentioning
confidence: 99%
“…Despite substantial evidence in support of TMH, providers' adoption of TMH had been slow pre-COVID-19 [13][14][15][16] . Poor adoption rates occurred despite signi cant investments and policy changes that encouraged use 14,17 .…”
Section: Discussionmentioning
confidence: 99%
“…25 There is limited evidence on telehealthcare-related education and training for practitioners. 26 A recent telehealthcare review identified complex domains such as privacy and security as aspects that may become increasingly important, and that care for chronic conditions and medication reviews are important for telemedicine services. 27 This study has demonstrated that complexity in consultations often left the trainees feeling under-confident, and that there was a positive correlation between the training received and the confidence to perform that particular competency independently.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%